Preoperative Erythrocyte Sedimentation Rate Independently Predicts Overall Survival in Localized Renal Cell Carcinoma following Radical Nephrectomy. (29th July 2012) - Cross, Brian W.; Johnson, Timothy V.; DeRosa, Austin B.; Ogan, Kenneth; Pattaras, John G.; Nieh, Peter T.; Kucuk, Omer; Harris, Wayne B.; Master, Viraj A.
Abstract : Objectives . To determine the relationship between preoperative erythrocyte sedimentation rate (ESR) and overall survival in localized renal cell carcinoma (RCC) following nephrectomy. Methods . 167 patients undergoing nephrectomy for localized RCC had ESR levels measured preoperatively. Receiver Operating Characteristics curves were used to determine Area Under the Curve and relative sensitivity and specificity of preoperative ESR in predicting overall survival. Cut-offs for low (0.0–20.0 mm/hr), intermediate (20.1–50.0 mm/hr), and high risk (>50.0 mm/hr) groups were created. Kaplan-Meier analysis was conducted to assess the univariate impact of these ESR-based groups on overall survival. Univariate and multivariate Cox regression analysis was conducted to assess the potential of these groups to predict overall survival, adjusting for other patient and tumor characteristics. Results . Overall, 55.2% were low risk, while 27.0% and 17.8% were intermediate and high risk, respectively. Median (95% CI) survival was 44.1 (42.6–45.5) months, 35.5 (32.3–38.8) months, and 32.1 (25.5–38.6) months, respectively. After controlling for other patient and tumor characteristics, intermediate and high risk groups experienced a 4.5-fold (HR: 4.509, 95% CI: 0.735–27.649) and 18.5-fold (HR: 18.531, 95% CI: 2.117–162.228) increased risk of overall mortality, respectively. Conclusion . Preoperative ESR values represent a robust predictor of overall survival following nephrectomy in localized RCC.